2018
DOI: 10.1002/ece3.4784
|View full text |Cite
|
Sign up to set email alerts
|

Bombus terrestris in a mass‐flowering pollinator‐dependent crop: A mutualistic relationship?

Abstract: Bumblebees (Bombus spp.) rely on an abundant and diverse selection of floral resources to meet their nutritional requirements. In farmed landscapes, mass‐flowering crops can provide an important forage resource for bumblebees, with increased visitation from bumblebees into mass‐flowering crops having an additional benefit to growers who require pollination services. This study explores the mutualistic relationship between Bombus terrestris L. (buff‐tailed bumblebee), a common species in European farmland, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
(67 reference statements)
1
14
0
Order By: Relevance
“…In any case, B. terrestris in the southern part of South America is still expanding its range, rapidly increasing across different habitats (i.e., sclerophyllous scrublands, dry forests, temperate rainforests, and the Patagonian steppe) in Argentina and Chile 23 , 25 , 26 . This super-generalist bumblebee can invade a wide range of habitats, taking advantage of a wide variety of flower resources 27 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…In any case, B. terrestris in the southern part of South America is still expanding its range, rapidly increasing across different habitats (i.e., sclerophyllous scrublands, dry forests, temperate rainforests, and the Patagonian steppe) in Argentina and Chile 23 , 25 , 26 . This super-generalist bumblebee can invade a wide range of habitats, taking advantage of a wide variety of flower resources 27 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…However, several varieties of Cucurbita pepo have been observed to set fruit in the absence of fertilisation, and therefore pollination, via parthenocarpy (Robinson & Reiners 1999;Kurtar 2003;Martínez et al 2013;Knapp & Osborne 2017). This genetic trait is desirable for growers in crops that are usually pollinator-dependent because fruit is able to form is conditions that are adverse for pollinators, potentially extending geographic and climatic ranges of production (Knapp et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Since the majority of cucurbit species are monoecious (Box 1), consideration must also be given to whether some pollinator species show a preference for either staminate or pistillate flowers which could significantly influence pollen transfer. Indeed, bee species have been shown to preferentially choose and forage for longer in staminate flowers as their nectar has a higher sugar content (Knapp et al 2018) and the nectaries are harder to access than pistillate flowers (Tepedino 1981;Phillips & Gardiner 2015). In the United Kingdom, Bombus terrestris L. has been shown to have a more equal preference for staminate (Fig.…”
Section: Citrullus Lanatusmentioning
confidence: 99%
“…Several studies have assessed the effects of a landscape on a particular bee species, generating mixed results. For example, B. terrestris in the presence of courgette ( Cucurbita pepo ) agro-ecosystems had high fidelity for nectar, but not for pollen [116]. Nonetheless, simulations of empirical data for nectar and pollen in the Bumble-BEEHAVE model revealed that early season courgette nectar increased the quantity of several colony endpoints.…”
Section: Habitat Destruction and Fragmentationmentioning
confidence: 99%
“…In bumble bees, it was found that maize monocultures provided B. terrestris with low-quality pollen that negatively impacted colony growth, while oilseed pollen fostered colony growth, but only when mass flowering occurred at the end of the bloom period [117]. Other monocultures can provide bees with only part of their necessary nutrition requirements [116], where courgette fields provided B. terrestris sufficient nectar, but not pollen. Furthermore, differences in the chemistry of floral food sources and their resulting effects on pollinating animals have been documented across plant cultivars, classifications, pollens, and nectars.…”
Section: Monoculture Plantingsmentioning
confidence: 99%